Study of High Energy Density Matter through Quantum Molecular Dynamics and Time Resolved X-ray Scattering - White, T (2014)
The warm dense matter regime (WDM), defined by temperatures of a few electron volts and densities comparable with solids, is a complex state of matter where multi-body particle correlations and quantum effects play an important role in determining the overall structure and equation of state. The study of WDM states represents the laboratory analogue of the astrophysical environments found in the cores of planets and in the crusts of old stars, but also has practical applications for controlled thermonuclear fusion. Time resolved X-ray diffraction is used to study the temporal evolution of a sample from solid state towards WDM, either after irradiation with an intense proton/electron beam, in carbon samples, or direct laser illumination, in thin gold nanofoils. The electron-ion equilibration time is extracted through the use of the two-temperature model and in highly excited carbon shown to be longer than previously thought, this is attributed to strong ion-ion coupling screening the interaction (coupled mode theory). Calculation of the dynamic ion-ion structure factor is performed using orbital-free density functional theory (OF-DFT) and shown to compare well with Kohn-Sham DFT in both the static and dynamic cases. Experimental verification of these results is vital and measurement of the microscopic dynamics of warm dense aluminium have been successfully demonstrated through inelastic X-ray scattering. Using the self-seeded beam at the linear coherent light source (LCLS) scattering at a small momentum exchange allowed the first direct measurement of ion acoustic waves in WDM. This data provides the basis for a direct experimental test of many dense plasma theories through direct comparison with the ion-ion dynamic structure factor.